Optimizing Fertilizer Use Efficiency for Crop Production - Gregoire Carai, Nekelia (Inter-American Institute for Cooperation on Agriculture (IICA), 2024)
Guest speaker: Dr. Gaius Eudoxie, Senior Lecturer in Soil Science at the University of the West Indies